Las estrategias didáctica y su influencia en el aprendizaje de lecto - escritura en el área de lengua y literatura de los estudiantes del segundo año de Educación General Básica en la Escuela "Manuelita Sáenz", del recinto Chalata Alto, parroquia Veintimilla, cantón Guaranda, provincia bolívar en el periodo lectivo 2010 - 2011 - Gaibor Mora, Angelita del Rocío (2011)
This research on. TEACHING STRATEGIES SY ITS INFLUENCE ON THE LEARNING OF READING - WRITING IN THE AREA OF LANGUAGE AND LITERATURE OF THE SECOND YEAR STUDENTS GENERAL EDUCATION BASIC SCHOOL "Manuela Sáenz" CHALATA PRECINCT HIGH VEINTIMILLA CHURCH, CANTON GUARANDA, Province BOLIVAR SCHOOL IN THE PERIOD 2010 - 2011 The Teaching for being in an enclosure that does not meet all standards for the academic development of methodological strategies that children apply meaningful learning, which is attached by a lack of teaching resources and not have training courses aimed at strengthening and developing the intellectual, spiritual, critical reflection and qualifying resulting in comfort and teaching becomes routine that prevents passing schemes, adapted to reality, since long time ago and limiting levels in the teaching and learning processes. The primary objective is to improve the learning of reading - writing, using appropriate strategies s teaching in the area of language and literature to assess the importance of language, and propose an interactive material to help develop new expectations of children. The tutorial in the classroom becomes a very important resource that puts the teacher within reach of everyday life as a tool to make knowledge accessible to students. This type of guide, improves knowledge in a practical, positive results in the institution. The thesis consists of an introductory part, which is the issue, presents the background, the problem, rationale, objectives, hypotheses and operationalization of variables corresponding to the overall presentation of the work. Chapter I contains the theoretical framework, this whole theory is developed regarding the research topic, considering the two variables of the hypothesis, in order to determine the causes and effects of the problem and to make research to teachers and students with to seek alternative solutions to the problem. Chapter II consists of the methodological framework, in which details: the type ofresearch, methods, techniques to be used in carrying out the work as well as population and sample to be studied to know the point of view with respect to the problem. Chapter III corresponds to the analysis of the results of research, here are the statistics in tabular and graphical representation in cakes, to proceed to analyze each of the questions. Allowing for the testing of the hypothesis, conclusions and recommendations. Chapter IV deals with the proposal, there arises the title, introduction, objectives to be